Design tool for offgrid hydrogen refuelling systems for aerospace applications. (1st February 2016) - Troncoso, E.; Lapeña-Rey, N.; Gonzalez, M.
Highlights: A simulation tool for offgrid CPV-based hydrogen refuelling systems is presented. Simulations of system configurations with specific UAS hydrogen demand scenarios. Regarding system size & reliability the most critical components are the CPV array and batteries. In terms of energy efficiency the most critical component is the electrolyser. Abstract: To develop an environmentally acceptable refuelling solution for fuel cell-powered unmanned aerial systems (UASs) to operate in remote areas, hydrogen fuel must be produced on-site from renewable energy sources. This paper describes a Matlab-based simulation tool specifically developed to pre-design offgrid hydrogen refuelling systems for UAS applications. The refuelling system comprises a high concentrated PV array (CPV), an electrolyser, a hydrogen buffer tank and a diaphragm hydrogen compressor. Small composite tanks are also included for fast refuelling of the UAV platforms at any time during the year. The novel approach of selecting a CPV power source is justified on the basis of minimizing the system footprint (versus flat plat or low concentration PV), aiming for a containerized remotely deployable UAS offgrid refuelling solution. To validate the simulation tool a number of simulations were performed using experimental data from a prototype offgrid hydrogen refuelling station for UAVs developed by Boeing Research & Technology Europe. Solar irradiation data for a selected location and daily UAS hydrogen demands of between 2.8 and 15.8 Nm 3 were employed as the primary inputs, in order to calculate a recommended system sizing solution and assess the expected operation of the refuelling system across a given year. The specific energy consumption of the refuelling system obtained from the simulations is between 5.6 and 8.9 kW he per kg of hydrogen delivered to the UAVs, being lower for larger daily hydrogen demands. Increasing the CPV area and electrolyser size in order to supply higher daily hydrogen demands (e.g., above 10 Nm 3 H2 per day) improves the system operability. However this can imply excessive system size and costs, jeopardizing the techno-economic feasibility of a remotely deployable off-grid refuelling solution.